Digitalization by means of a prototyping process : the case of a Brazilian public service - Gardenghi, John Lenon Cardoso (2020)
Digital Transformation is under constant evolution. Organizations that were not already created in the digital environment need to digitalize their services. The process used to do so may involve not only elements of technology, but also social, political and organizational aspects. While there is no holistic method to implement digital transformation, organizations learn from successful cases in order to build their own way to implement digital transformation. This paper presents the process through which a physically delivered service provided by the Brazilian federal government was transformed into a digital service. This was performed with a prototyping approach made of six steps: diagnose the service, analyze the service, identify the requirements, and elaborate, verify, and validate the prototype. To perform the digitalization, an automation tool was used, and there was constant interaction with the service provider. This article offers a detailed process to implement digitalization by means of prototyping, which can be used by other organizations to make services digital.